Dendrochronology in European Russia in the Early 21st Century: State of the Art - Solomina, Olga; Matskovsky, Vladimir (Frontiers in Ecology and Evolution, 2021)
In this review we have focused on the following key points: 1. Living trees in European Russia and their climatic sensitivity. Species suitable for tree-ring analyses, their age limits, spatial distribution of temperature- and drought-sensitive trees, available tree-ring chronologies. 2. Extension of the living-trees chronologies using archeological and architectural samples. Dendrochronological dating of archeological and cultural monuments. 3. Tree-ring-based climatic reconstructions in European Russia. European Russia Drought Atlas. 4. Climatic and environmental reconstructions in the Northern Caucasus. 5. Dendroecology. We also briefly summarized the problems and prospects of tree-ring research in European Russia.